Laser Additive Manufacturing with Crack‐sensitive Materials. Issue 2 (April 2015) - Brückner, Frank; Finaske, Thomas; Willner, Robin; Seidel, André; Nowotny, Steffen; Leyens, Christoph; Beyer, Eckhard
Abstract Laser additive manufacturing is state‐of‐the‐art and regarded as a key technology in the future of production engineering [1]. Originating from a computer model, a new freedom of design can be achieved by simply adding layer by layer. Beyond the new perspectives and extended possibilities of conventional processes there are fields of application which already have been opened up. One of those is the highly innovative but demanding field of processing with heat resisting alloys (see Fig. 1). This field of engineering has traditionally been a door opener for hightech technologies such as aerospace or energy [2, 3].